The Relationship Between Physical Activity and Diet and the Incidence of Diabetes Mellitus in the Elderly in Kampung Baru Village - Rahmadini, Mutia; Aziza, Nurul; Noviani (Sekolah Tinggi Ilmu Kesehatan Sapta Bakti, 2025)
Diabetes mellitus (DM) is a chronic disease characterized by hyperglycemia and glucose intolerance caused by the pancreas' inability to produce insulin accurately or the body's inability to effectively use the insulin it produces. According to the International Diabetes Federation (IDF), the global incidence of diabetes reached 424.9 million in 2017, and this number is predicted to reach 628.6 million by 2045. This study aims to determine the relationship between physical activity and diet and the incidence of diabetes in the elderly. This study used a quantitative approach with a cross-sectional design. The sample was determined using purposive sampling, resulting in 57 samples. The data collection tool used was a questionnaire, which was then analyzed using the chi-square test. The statistical test results showed a significant relationship between physical activity and the incidence of diabetes in the elderly in Kampung Baru Village with a p-value of 0.009 (p-value <0.05). And there is a significant relationship between diet and the incidence of diabetes in the elderly in Kampung Baru village with a p-value = 0.011 (p-value = 0.05).